The costs of 'free': Experiences of facility-based childbirth after Benin's caesarean section exemption policy. (November 2016) - Lange, Isabelle L.; Kanhonou, Lydie; Goufodji, Sourou; Ronsmans, Carine; Filippi, Véronique
Abstract: As one of many similar policies in the region, in 2009 Benin launched a free c-section policy in publicly funded hospitals intended to decrease the barriers to facility delivery and the heavy financial burdens on women and their families. We conducted a qualitative study for eight months between 2012 and 2014 to understand women's experiences of care in maternity wards. We carried out semi-structured interviews with 30 women who had delivered via c-section at five hospitals. Two of these hospitals became case study sites where in-depth research was undertaken that consisted of participant observation in each maternity ward and 32 further interviews with women who had complicated, vaginal and c-section deliveries. Overall, women continue to pay for care, both in the form of under-the-table payments to health workers and prescribed payments for services not covered by the policy, though they consider the costs reasonable compared to what the charges were before. Lifting the fees has facilitated conditions for midwives to alert doctors that the procedure might be needed. Partly because c-sections are still feared by most women, in one hospital this led to some women perceiving them as a threat if their labour was progressing more slowly. Implementation of the policy differed greatly between the two case study hospitals. We conclude that some burdens on women's access to care have been addressed but deterrents remain to the improved perception of quality of care on the part of women. Findings detail how important context is to the implementation of the policy, and suggest that similar user-fee removal policies should be accompanied by other measures addressing staff management and quality of care. Highlights: Ethnographic study of childbirth in two hospitals after the introduction of Benin's c-section policy. C-sections, largely undesired in Benin, still carry a hefty personal and financial cost for women. The implementation of an exemption policy can exacerbate already existing poor practices in hospitals. Maternal health exemption policies should be accompanied by measures for external support and supervision.